The impact of corporate social responsibility and internal controls on stakeholders' view of the firm and financial performance. Issue 3 (3rd July 2017) - Akisik, Orhan; Gal, Graham
Abstract : Purpose: The purpose of this study is to empirically examine whether two major stakeholder groups – customers and employees – consider third party-reviewed corporate social responsibility (CSR) reports and assurance on the quality of internal controls as value determinant in their decisions, and how their decisions influence financial performance through the halo effect of these reports. Design/methodology/approach: Using Compustat North America and Global Reporting Initiative data, the authors used first-order autoregressive models over the period from 2006 to 2012. Findings: The results indicate that the impacts of customers and employees on financial performance are influenced by third party-reviewed CSR reports and effective internal control. Moreover, it is found that the third party-reviewed CSR reports and effective internal control enable the persistence of financial performance. Social implications: The findings have implications for stakeholders in terms of third party-reviewed CSR reports and effective internal control. The findings are important due to the influence that these stakeholders (customers and employees) have on the financial performance of firms and the impact that CSR actions can have on society as a whole. Originality/value: To the authors' knowledge, this is the first study that contributes to the literature by demonstrating that information about third party-reviewed CSR reports and internal control reviews may influence the perceptions of firms by two primary stakeholders – customers and employees.